2007
DOI: 10.1002/dev.20182
|View full text |Cite
|
Sign up to set email alerts
|

Task constraints on preschool children's grip configurations during drawing

Abstract: Traditional accounts of motor development have described the development of grip configurations in terms of a global maturational change from immature to mature grips. We present data that demonstrate that the grip configurations of preschool-aged children are greatly influenced by task demands and are more variable than previous research has suggested. Grip configurations were most variable during free drawing. Three- to 4-year-olds with highly variable grips produced poorer quality drawings in a shape copyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Rather, our results argue for a multifactor process heavily reliant on infants gaining information via object exploration. Indeed, it is clear that through visual and haptic exploration, infants become increasingly sensitive to task oriented constraints such as the range of object qualities during the 2nd half of the first year (Braswell et al, 2007;Corbetta, Williams, & Snapp-Childs, 2006;Gibson, 1988;Gibson & Walker, 1984;Lederman & Klatzky, 1987). To be clear, by 'developmental window' we do not mean a 'sensitive' or 'critical' period, but are simply highlighting the period between when right left asymmetries are and are not clearly evident in relation to arm movements with and without a toy present.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, our results argue for a multifactor process heavily reliant on infants gaining information via object exploration. Indeed, it is clear that through visual and haptic exploration, infants become increasingly sensitive to task oriented constraints such as the range of object qualities during the 2nd half of the first year (Braswell et al, 2007;Corbetta, Williams, & Snapp-Childs, 2006;Gibson, 1988;Gibson & Walker, 1984;Lederman & Klatzky, 1987). To be clear, by 'developmental window' we do not mean a 'sensitive' or 'critical' period, but are simply highlighting the period between when right left asymmetries are and are not clearly evident in relation to arm movements with and without a toy present.…”
Section: Discussionmentioning
confidence: 99%
“…Among others, they used the mature standard tripod grasp in which the object is held between the thumb and the first two fingers. The proportion of tripod grasps increased with age (see Braswell & Rosengren, 2008;Braswell, Rosengren, & Peirroutsakos, 2007). A grip was scored as overhand when children grasped the pencil thumb down and forefinger up.…”
Section: Percentage Of Success Analysismentioning
confidence: 99%
“…Children have to learn to handle writing/drawing implements, and this is something that many of them find difficult (Connolly & Dagleish, 1989). Previous studies have shown that there is considerable variability in the manner in which children hold pens and pencils (see, for example, Blöte, Zielstra, & Zoetewey, 1987;Braswell, Rosengren, & Pierroutsakos, 2007;Connolly & Dagleish, 1989), and this affects the quality of their graphic production (Braswell et al, 2007;Martlew, 1992). As iPads allow for finger drawing, and are now making inroads into schools, it is worth testing whether their ease of use and immediacy actually improve the quality of drawings produced in an educational context.…”
mentioning
confidence: 99%